2018
DOI: 10.1590/0074-02760180086
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localisation of FLAG tagged enzymes of the dynamic protein S-palmitoylation cycle of Trypanosoma cruzi epimastigotes

Abstract: Dynamic S-palmitoylation of proteins is the addition of palmitic acid by zDHHC palmitoyl transferases (PATs) and depalmitoylation by palmitoyl protein thioesterases (PPTs). A putative PAT (TcPAT1) has been previously identified in Trypanosoma cruzi, the etiological agent of Chagas disease. Here we analyse other 14 putative TcPATs and 2 PPTs in the parasite genome. T. cruzi cell lines expressing TcPATs and TcPPTs plus a FLAG tag at the C terminus were produced for most enzymes, with positive detection by indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The repertoire of T. cruzi palmitoyl transferases (PATs) was first checked and 15 putative proteins were found [ 27 ], which agrees with Goldston and coworkers [ 28 ]. All respective genes, except for TcPAT6, were successfully isolated by PCR, thus indicating that T. cruzi has the palmitoylation machinery in its genome.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The repertoire of T. cruzi palmitoyl transferases (PATs) was first checked and 15 putative proteins were found [ 27 ], which agrees with Goldston and coworkers [ 28 ]. All respective genes, except for TcPAT6, were successfully isolated by PCR, thus indicating that T. cruzi has the palmitoylation machinery in its genome.…”
Section: Discussionsupporting
confidence: 62%
“…All respective genes, except for TcPAT6, were successfully isolated by PCR, thus indicating that T. cruzi has the palmitoylation machinery in its genome. Indeed, dynamic S-palmitoylation machinery could be expressed in T. cruzi epimastigotes [ 27 ]. Therefore, 2-BP could be exploited to gain some information on this lipid modification in this parasite, since it has been already demonstrated that 2-BP inhibits some PATs in T. brucei [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations